MASS CIRCUMCISION CULTURE VIEWED FROM EDUCATION - Abdul Shomad; Fitri Aulia Novita (International Jurnal of Education Schoolars, 2022)
Research on educational values in mass circumcision culture in Segobang Village, Licin District, Banyuwangi Regency will be carried out in 2021, the aim of which is to expose the culture in Segobang Village, Licin District, Banyuwangi Regency and study the values contained in mass circumcision culture in Segobang Village. Licin District, Banyuwangi Regency. The method used is descriptive qualitative descriptive qualitative research itself is a research method used to describe or analyze a research result but not used to make broader conclusions. Qualitative research itself is research that is descriptive in nature and tends to use analysis and aims to provide an explanation of a phenomenon and find or construct a theory related to a phenomenon with a historical approach. The results of the study show that the values contained in mass circumcision culture cover three aspects, namely cognitive, affective and psychomotor